Seismic behavior of irregular buildings in plan considering isolation systems with stiffness eccentricity - Garrido, Cesar (2024)
This research aims to evaluate the effect of the dynamic parameters of the isolation system (the degree of torsional coupling [Wb], the period of vibration [Tb], the critical damping ratio [xb], and the stiffness eccentricity of the isolation base [erb]) on the torsional behavior of a six-story reinforced concrete building family, considering the stiffness or mass eccentricities (er or em, respectively) in the superstructure. These modify structural behavior under severe earthquakes and increase lateral displacements and drifts. For this purpose, a nonlinear time-history analysis was performed on each model by subjecting them to a set of seven seismic accelerations records, measured on the coast of Peru and Chile, which were scaled following the pseudo-acceleration design spectrum from Peru. The main global responses were the maximum lateral displacements and the inter-story drifts. It was observed that the effect of em generated more amplification on lateral displacements and drifts than er. In a similar way, the parameter erb was very influential on the torsional behavior of the isolated buildings with em and er, amplifying lateral displacements up to 50 %. In addition, the parameter Tb impacted mostly on the inter-story drifts, reducing it up to 55 %. On the other hand, the parameters Wb and xb did not significantly influence the responses of interest.